L-Carnitine Reduces Oxidative Stress and Promotes Cells Differentiation and Bone Matrix Proteins Expression in Human Osteoblast-Like Cells. (20th January 2019) - Terruzzi, Ileana; Montesano, Anna; Senesi, Pamela; Villa, Isabella; Ferraretto, Anita; Bottani, Michela; Vacante, Fernanda; Spinello, Alice; Bolamperti, Simona; Luzi, Livio; Rubinacci, Alessandro
Abstract : Bone fragility and associated fracture risk are major problems in aging. Oxidative stress and mitochondrial dysfunction play a key role in the development of bone fragility. Mitochondrial dysfunction is closely associated with excessive production of reactive oxygen species (ROS). L-Carnitine (L-C), a fundamental cofactor in lipid metabolism, has an important antioxidant property. Several studies have shown how L-C enhances osteoblastic proliferation and activity. In the current study, we investigated the potential effects of L-C on mitochondrial activity, ROS production, and gene expression involved in osteoblastic differentiation using osteoblast-like cells (hOBs) derived from elderly patients. The effect of 5mM L-C treatment on mitochondrial activity and L-C antioxidant activity was studied by ROS production evaluation and cell-based antioxidant activity assay. The possible effects of L-C on hOBs differentiation were assessed by analyzing gene and protein expression by Real Time PCR and western blotting, respectively. L-C enhanced mitochondrial activity and improved antioxidant defense of hOBs. Furthermore, L-C increased the phosphorylation of Ca 2+ /calmodulin-dependent protein kinase II. Additionally, L-C induced the phosphorylation of ERK1/2 and AKT and the main kinases involved in osteoblastic differentiation and upregulated the expression of osteogenic related genes, RUNX2, osterix (OSX), bone sialoprotein (BSP), and osteopontin (OPN) as well as OPN protein synthesis, suggesting that L-C exerts a positive modulation of key osteogenic factors. In conclusion, L-C supplementation could represent a possible adjuvant in the treatment of bone fragility, counteracting oxidative phenomena and promoting bone quality maintenance.